Optimization of Culture Media and Acclimatization Techniques for Efficient Micropropagation of Economically Important Bamboo Species - Patel Parvej Pirpasha,; Dr. Byju John,; Dr. Suchitra Ku Panigrahy, (International Journal of Scientific Research in Science and Technology, 2025)
Bamboo has earned the colloquial name "green gold" because it is one of the most versatile plants that growth at such a terrific rate and possess immense ecological as well as economic benefits. Nevertheless, the plant faces a great challenge of limited availability of good quality planting material and also by complex traditional propagation methods. For this reason, this study was conducted to investigate cost-effective in vitro propagation techniques for bamboo cultivars to overcome such limitations and promote sustainable cultivation. The study aims at exploring the feasibility of different tissue culture techniques, such as axillary shoot proliferation, somatic embryogenesis, and micro propagation with the focus on the medium content optimization and hormonal treatment. This study therefore contributes to the storehouse of knowledge by establishing the potential of low-cost in vitro propagation as a viable means toward sustainable bamboo culture. Optimizing tissue culture techniques and an alternative nutrient media for this research purpose is expected to provide a feasible solution for the large-scale production of bamboo, thereby supporting afforestation efforts, carbon sequestration, and economic development of bamboo- dependent communities.
Keywords: Bamboo; In-vitro propagation; Axillary; shoot; proliferation; Somatic; embryogenesis; Micro propagation; Tissue culture Sustainable; cultivation; Hormonal; treatments; Genetic; uniformity; Cost; effective; techniques